Two new phenolic glucosides from marine-derived fungus Aspergillus sp. Issue 13 (1st July 2022) - Wen, Huiling; Zang, Yi; Zhu, Qianheng; Ouyang, Sheng; Luo, Juanjuan; Luo, Nianhua; Zhu, Hucheng; Zhang, Yonghui
Abstract: Two new phenolic glucosides, including a new O -glycoside (1 ) and a new C -glycoside (2 ), were isolated from a marine-derived fungus Aspergillus sp. The structures of new compounds were elucidated through interpretations of spectroscopic evidence and high-resolution electrospray ionization mass spectrometry. The hexose unit of 1 was identified as β -D-glucose by comparison with an authentic sample via HPLC after acid hydrolysis and derivatization. All compounds were evaluated for their ability to inhibit LPS-induced NO production in RAW264.7 macrophages, but none of them displayed significant activity. Graphical Abstract: UF0001